Case Report: Remote magnetic navigation and accessory pathways ablation in a single ventricle young adult with complex corrective surgeries - Paja, Steliana Cosmina; Gondoș, Viviana; Deaconu, Silvia; Cinteză, Eliza; Vătășescu, Radu (Frontiers in Pediatrics, 2024)
Supraventricular arrhythmias have become an increasingly significant contributor to the risk of mortality and morbidity in adults with complex congenital heart disease (CHD), especially in light of recent advances in palliative corrective surgeries. Because of their unique characteristics, they demand specific treatment approaches. While pharmaco-logical interventions are an option, they have limited effectiveness and may lead to side effects. Although performing radiofrequency ablation (RFA) can be exceptionally challenging in patients with complex CHD, due to particular vascular access and also modified anatomy, it has paved the way to enhance comprehension of the underlying mechanisms of supraventricular arrhythmias. This, in turn, enables the provision of improved therapies and, ultimately, an enhancement in the quality of life and symptom management for these patients. The purpose of this case report is to highlight the benefits of utilizing advanced technologies such as three-dimensional electro-anatomical mapping systems, remote magnetic navigation, and highly flexible mapping and ablation catheters during RFA in a young adult with complex congenital heart disease. Although he lacked venous connections to the right atrium (RA) due to multiple corrective surgeries we, remarkably, were capable to advance a decapolar deflectable diagnostic catheter inside the Fontan tunnel and from there to record and stimulate the RA. Successful ablation of two accessory pathways was achieved with no arrhythmia recurrence during follow-up.